Palmitoylethanolamide: A Multifunctional Molecule for Neuroprotection, Chronic Pain, and Immune Modulation - Valeria Di Stefano; Luca Steardo; Martina D’Angelo; Francesco Monaco; Luca Steardo (Biomedicines, 2025)
Palmitoylethanolamide (PEA) is an endogenous lipid mediator belonging to the N-acyl-ethanolamine family, widely recognized for its multifaceted effects on neuroprotection, chronic pain management, and immune modulation. As a naturally occurring compound, PEA plays a crucial role in maintaining homeostasis under conditions of cellular stress and inflammation. Its pharmacological effects are primarily mediated through peroxisome proliferator-activated receptor-alpha (PPAR-α) activation, alongside indirect modulation of cannabinoid receptors CB1 and CB2, as well as interactions with novel targets such as GPR55 and TRPV1. These molecular mechanisms underpin its broad therapeutic potential, particularly in the management of neuroinflammatory and neurodegenerative disorders, pain syndromes, and immune dysregulation. A major advancement in PEA research has been the development of ultramicronized palmitoylethanolamide (umPEA), which significantly enhances its bioavailability and therapeutic efficacy by facilitating better tissue absorption and interaction with key molecular pathways. Preclinical and clinical studies have demonstrated that umPEA is particularly effective in reducing neuroinflammation, stabilizing mast cells, and enhancing endocannabinoid system activity, making it a promising candidate for integrative approaches in neuropsychiatric and chronic inflammatory diseases. Given its well-established safety profile, umPEA represents an attractive alternative or adjunct to conventional anti-inflammatory and analgesic therapies. This communication provides a comprehensive overview of the mechanisms of action and therapeutic applications of both PEA and umPEA, emphasizing their emerging role in clinical practice and personalized medicine.